Use of statistical parametric mapping of 18F-FDG-PET in frontal lobe epilepsy - Plotkin, M.; Amthauer, H.; Merschhemke, M.; Lüdemann, L.; Hartkop, E.; Ruf, J.; Gutberlet, M.; Bertram, H.; Meencke, H.-J.; Felix, R.; Venz, St. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: Evaluation of the use of statistical parametrical mapping (SPM) of FDG-PET for seizure lateralization in frontal lobe epilepsy. Patients: 38 patients with suspected frontal lobe epilepsy supported by clinical findings and video-EEG monitoring. Method: Statistical parametrical maps were generated by subtraction of individual scans from a control group, formed by 16 patients with negative neurological/psychiatric history and no abnormalities in the MR scan. The scans were also analyzed visually as well as semiquantitatively by manually drawn ROIs. Results: SPM showed a better accordance to the results of surface EEG monitoring compared with visual scan analysis and ROI quantification. In comparison with intracranial EEG recordings, the best performance was achieved by combining the ROI based quantification with SPM analysis. Conclusion: These findings suggest that SPM analysis of FDG-PET data could be a useful as complementary tool in the evaluation of seizure focus lateralization in patients with supposed frontal lobe epilepsy.
Keywords: Statistical parametrical mapping; Fluorine-18-Fluorodeoxyglucose; positron emission tomography; frontal lobe epilepsy